A method for improving the coercive force of NdFeB magnets by power ultrasonic treatment
By using contact-introduced power ultrasonic treatment during the heat treatment of NdFeB-based magnets, the distribution of rare earth elements and grain boundary structure are optimized, and the problem of insufficient coercive force of NdFeB-based magnets in the prior art is solved, and the effect of significantly improving coercive force and grain boundary uniformity is achieved.
Patent Information
- Application Number
- CN202411929989.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
It is difficult for existing neodymium iron boron-based magnets to effectively optimize the magnetic phase, grain boundary structure and rare earth element distribution in the sintering process, resulting in insufficient coercive force of magnetic properties.
During the heat treatment process of NdFeB system sintered magnets, contact-introduced power ultrasonic treatment is used to change the physical and chemical environment in the high-temperature melt or solid phase through ultrasonic waves, and optimize the distribution of rare earth elements and grain boundary structure morphology.
The coercive force of neodymium iron boron-based magnets has been significantly improved, the proportion of rare earth-rich phases in grain boundary structures has increased to 21.2%, and the intrinsic coercive force Hcj has increased by 20.8%, making the grain boundary clearer and more uniform.
Smart Images

Figure CN119361318B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnets, and in particular to a method for improving the coercive force of a NdFeB magnet by power ultrasonic treatment. Background Art
[0002] Among permanent magnet materials, NdFeB magnets have the best comprehensive performance and are key magnetic functional materials supporting the development of new energy vehicles, rail transportation and other industries. The current preparation method of NdFeB magnets is mainly liquid phase sintering. During the sintering process, RE2Fe 14 The B magnetic phase is solid and the grain boundary structure is liquid. By regulating the sintering process, the morphology of the magnetic phase grains, grain boundary structure, and the distribution of rare earth elements can be optimized, thereby improving the magnetic properties such as the coercive force of the sintered magnet and its service performance.
[0003] Existing research results show that the distribution of rare earth elements, grain boundary structure morphology, grain boundary phase content and its distribution in NdFeB magnets are key factors affecting magnetic properties. In the existing technology, the wettability between the liquid grain boundary structure and the magnetic phase, element diffusion, and even the solidification path of the liquid grain boundary structure are generally controlled by adjusting parameters such as element ratio, sintering temperature, sintering time, and cooling method, so as to optimize the distribution of rare earth elements, grain boundary structure morphology, grain boundary phase content and distribution. For example, the Chinese patent "A method for preparing high-performance sintered NdFeB magnets" (CN111243806A, published on June 5, 2020) enhances magnetic properties such as coercivity by increasing the density before sintering and reducing the sintering temperature; the Chinese patent "A grain boundary diffusion process for NdFeB magnets and a method for preparing NdFeB magnets" (CN114188143A, published on March 15, 2022) uses the molten grain boundary structure as an element diffusion channel to optimize the element distribution of the sintered magnet and improve the magnetic properties. However, only adjusting the alloy composition and liquid phase sintering parameters has limited optimization effect on the magnetic phase, grain boundary structure micromorphology and internal rare earth element distribution, and requires a longer heat treatment time to obtain the best microstructure characteristics. In addition, the shortcomings of the traditional sintering process also include: too low sintering temperature or too short sintering time will lead to insufficient diffusion of rare earth elements, and over-sintering will eliminate the structure of non-uniform distribution of rare earth elements; the grain boundary structure morphology and grain boundary phase distribution are closely related to crystal nucleation and growth, but the air cooling process of the sintering process is difficult to control the nucleation and growth of liquid grain boundary structure, which restricts the efficient optimization of the magnetic properties of NdFeB magnets. Therefore, it is necessary to introduce a new diffusion control method other than heat control to significantly improve its magnetic properties such as coercivity. Summary of the invention
[0004] The purpose of the present invention is to provide a method for improving the coercive force of NdFeB magnets by power ultrasonic treatment. The method provided by the present invention can further improve the coercive force of NdFeB magnets.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for improving the coercive force of NdFeB magnets by power ultrasonic treatment, wherein the power ultrasonic treatment is introduced in a contact manner during the heat preservation process of the NdFeB sintered magnets.
[0007] The method for improving the coercive force of NdFeB magnets by power ultrasonic treatment comprises:
[0008] The NdFeB sintered magnet is subjected to a first heat treatment, a second heat treatment and a third heat treatment in sequence to obtain a high coercive force NdFeB magnet; during the heat preservation process of at least one of the first heat treatment, the second heat treatment and the third heat treatment, contact-introduced power ultrasonic treatment is performed.
[0009] Preferably, the power ultrasound is applied to the NdFeB sintered magnet in a contact manner through an ultrasonic system; the ultrasonic system includes a horn and a mandrel; the NdFeB sintered magnet is fixed between the horn and the mandrel; the contact between the horn and the mandrel and the NdFeB sintered magnet is a rigid contact; the contact pressure between the horn and the mandrel and the NdFeB sintered magnet is not less than 1.0×10 6 The contact area between the horn and the top rod and the NdFeB sintered magnet is independently not less than 10mm 2 .
[0010] Preferably, the shape of the NdFeB sintered magnet is to have at least two parallel end faces, and the two parallel end faces have an overlapping portion in projection; the area of the overlapping portion is not less than 10 mm 2 .
[0011] Preferably, the temperature of the first heat treatment is 1000-1100° C., the holding time of the first heat treatment is 0.5-4 h, and the time of the power ultrasound in the first heat treatment is ≤ the holding time of the first heat treatment.
[0012] Preferably, the temperature of the second heat treatment is 800-950° C., the holding time of the second heat treatment is 2-3 hours, and the time of the power ultrasound in the second heat treatment is ≤ the holding time of the second heat treatment.
[0013] Preferably, the temperature of the third heat treatment is 400-600° C., the holding time of the third heat treatment is 3-4 hours, and the time of the power ultrasound in the third heat treatment is ≤ the holding time of the third heat treatment.
[0014] Preferably, the power ultrasound includes continuous ultrasound or pulsed ultrasound; the ultrasound power density of the power ultrasound is (1-65)×10 4 W / m3 The ultrasonic frequency of power ultrasound is 10~500kHz.
[0015] Preferably, the first heat treatment, the second heat treatment and the third heat treatment are all performed under an inert atmosphere; the pressure of the inert atmosphere is less than 1×10 -2 Pa.
[0016] Preferably, the cooling rates of the first heat treatment, the second heat treatment and the third heat treatment are independently greater than 20° C. / min.
[0017] Preferably, the cooling methods of the first heat treatment, the second heat treatment and the third heat treatment are independently air cooling or liquid quenching; the cooling medium used for the liquid quenching is water, oil or liquid alloy.
[0018] The present invention provides a method for improving the coercive force of NdFeB magnets by power ultrasonic treatment, wherein contact-introduced power ultrasonic treatment is performed during the heat preservation process of heat treatment of NdFeB sintered magnets; the method for improving the coercive force of NdFeB magnets by power ultrasonic treatment comprises: sequentially performing a first heat treatment, a second heat treatment and a third heat treatment on the NdFeB sintered magnets to obtain a high coercive force NdFeB magnet; and contact-introduced power ultrasonic treatment is performed during the heat preservation process of at least one of the first heat treatment, the second heat treatment and the third heat treatment. The present invention heat treats the NdFeB sintered magnets and performs power ultrasonic treatment during the heat preservation process, using ultrasonic waves to change the physical and chemical environment in the high-temperature melt or solid phase, optimize the distribution of rare earth elements, promote the formation of uniform and continuous grain boundary structures, and optimize the content of the rare earth-rich phase (α(RE)) and its distribution in the grain boundary structure, thereby improving the coercive force of the NdFeB magnets. The results of the embodiment show that the method provided by the present invention can significantly increase the volume proportion of the rare earth-rich phase (α(RE)) in the grain boundary structure of the NdFeB magnet, which can reach 21.2%, which is 87.6% higher than that of the NdFeB magnet without power ultrasound. At the same time, the grain boundary is clearer, indicating that the rare earth-rich phase (α(RE)) is more evenly distributed at the grain boundary; the intrinsic coercive force H cj It can reach 11.79kOe, which is 20.8% higher than that of NdFeB magnets without power ultrasound, and can further improve the coercive force of NdFeB magnets.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention introduces ultrasound during the magnet heat treatment process, and uses ultrasonic energy to change the solid magnetic phase RE2Fe 14B. The physical and chemical environment within the liquid grain boundary structure miscible system affects the diffusion of rare earth elements, the wettability of the solid-liquid interface, and the crystal nucleation at the grain boundary, thereby optimizing the distribution of rare earth elements, promoting the formation of uniform and continuous grain boundary structure, regulating the grain boundary structure morphology and the grain boundary phase content and its distribution, and improving the coercive force and other properties of NdFeB magnets. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The temperature gradient diagram of sintering, first heat treatment, second heat treatment and third heat treatment in the embodiment of the present invention;
[0022] Figure 2 This is a SEM image of the high coercivity NdFeB magnet prepared in Example 1 of the present invention;
[0023] Figure 3 This is a SEM image of a high coercive force NdFeB magnet prepared in Example 2 of the present invention;
[0024] Figure 4 This is a SEM image of the high coercivity NdFeB magnet prepared in Example 3 of the present invention;
[0025] Figure 5 This is a SEM image of the NdFeB magnet prepared in Comparative Example 1 of the present invention;
[0026] Figure 6 It is a curve diagram of the proportion of α(RE) phase in the grain boundary structure of the NdFeB magnets prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides a method for improving the coercive force of NdFeB magnets by power ultrasonic treatment, wherein the power ultrasonic treatment is introduced in a contact manner during the heat preservation process of the NdFeB sintered magnets.
[0028] The method for improving the coercive force of NdFeB magnets by power ultrasonic treatment comprises:
[0029] The NdFeB sintered magnet is subjected to a first heat treatment, a second heat treatment and a third heat treatment in sequence to obtain a high coercive force NdFeB magnet; during the heat preservation process of at least one of the first heat treatment, the second heat treatment and the third heat treatment, contact-introduced power ultrasonic treatment is performed.
[0030] In the present invention, the shape of the NdFeB sintered magnet is to have at least two parallel end faces, and the two parallel end faces have an overlapping portion in projection; the area of the overlapping portion is not less than 10mm 2The present invention limits the shape of the NdFeB sintered magnet to the above range to ensure that the horn and the mandrel of the power ultrasound can stably clamp the NdFeB sintered magnet during subsequent power ultrasound.
[0031] In the present invention, the NdFeB sintered magnet is preferably obtained by pressing and sintering RE-Fe-B alloy powder.
[0032] In the present invention, the RE in the RE-Fe-B alloy powder includes at least Nd. The present invention has no special requirements on the types and contents of other rare earth elements in the RE-Fe-B alloy powder, and the rare earth elements and contents commonly used in magnet preparation in the art can be used.
[0033] In the present invention, the RE-Fe-B alloy powder can be a mixed powder of a plurality of RE-Fe-B alloy powders containing Nd element. The present invention has no particular limitation on the mixing ratio of the mixed powder, and any mixing ratio can be adopted.
[0034] The present invention limits the RE in the RE-Fe-B alloy powder to at least include Nd, which can ensure that the NdFeB magnet has good comprehensive performance.
[0035] In the present invention, the pressing molding is preferably carried out under the conditions of alternating magnetic field and isostatic pressing. The present invention has no special restrictions on the parameters of the alternating magnetic field, and the parameters can be adjusted accordingly according to the density and the orientation of the magnetic phase grains. In the present invention, the pressure of the isostatic pressing is preferably 150~200MPa, and more preferably 180MPa. The present invention performs pressing under the conditions of alternating magnetic field and isostatic pressing to improve the density and orientation of the green compact, thereby improving the orientation of the sintered magnet, and improving the coercive force and remanence of the magnet.
[0036] In the present invention, the sintering is preferably carried out under an inert atmosphere; the inert atmosphere is preferably argon and / or helium. When the inert atmosphere is argon and helium, the present invention has no special restrictions on the mixing ratio of the argon and helium, and any ratio can be used. In the present invention, the pressure of the inert atmosphere is preferably <1×10 -2 Pa. In the present invention, the parameters of the inert atmosphere are limited to the above range to ensure that the magnet has good performance.
[0037] The present invention has no special limitation on the sintering equipment, and any equipment commonly used by those skilled in the art that can achieve sintering in an inert atmosphere and under a high vacuum degree can be used.
[0038] In the present invention, the sintering is preferably gradient sintering; the gradient sintering preferably includes a first heating, a first insulation, a second heating, a second insulation, a third heating, a third insulation, a fourth heating and a fourth insulation performed in sequence; the temperature of the first insulation is preferably 300-400°C, more preferably 330-350°C; the time of the first insulation is preferably 1-2h, more preferably 1-1.5h; the temperature of the second insulation is preferably 500-600°C, more preferably 550-600°C; the time of the second insulation is preferably 1-2h, more preferably 1.5-2h; the temperature of the third insulation is preferably 750-900°C, more preferably 800-850°C; the time of the third insulation is preferably 2-4h, more preferably 2.5-3h; the temperature of the fourth insulation is preferably 1000-1100°C, more preferably 1050°C; the time of the fourth insulation is preferably 0.5-6h, more preferably 2-4h, further preferably 2-3h. In the present invention, the heating rates of the first, second, third and fourth heating are preferably independently 5-20°C / min, more preferably 10-15°C / min. In the first heat preservation process, the present invention discharges H2O, O2 and N2 adsorbed on the surface, and discharges the impurity gases of additives such as antioxidants and lubricants during the second heat preservation process, while the residual NdH x The decomposition and discharge of hydrogen, the grain boundary structure melts and fills the gaps between the magnetic phase grains in the third heat preservation process, and the magnet is rapidly densified in the fourth heat preservation process. The present invention limits the temperature, time and heating rate of each stage of sintering to the above range, so that the NdFeB magnet has good magnetic properties.
[0039] In the present invention, after the fourth heat preservation of the sintering is completed, the product of the fourth heat preservation is preferably cooled; in the present invention, the cooling rate of the cooling is preferably >20°C / min; the cooling method of the cooling is preferably air cooling or liquid quenching; the cooling medium used for the liquid quenching is preferably water, oil or liquid alloy. In a specific embodiment of the present invention, the liquid alloy is a Ga-In-Sn liquid alloy. The present invention limits the cooling parameters in the sintering to the above range to obtain a NdFeB magnet with good performance.
[0040] In the present invention, contact-introduced power ultrasonic treatment is carried out during the insulation process of at least one of the first heat treatment, the second heat treatment and the third heat treatment. Preferably, contact-introduced power ultrasonic treatment is carried out during the insulation process of at least two of the first heat treatment, the second heat treatment and the third heat treatment. More preferably, contact-introduced power ultrasonic treatment is carried out during the insulation process of all of the first heat treatment, the second heat treatment and the third heat treatment.
[0041] In the present invention, the power ultrasound is preferably applied to the NdFeB sintered magnet by contacting through an ultrasonic system; the ultrasonic system preferably includes a horn and a mandrel; the NdFeB sintered magnet is preferably fixed between the horn and the mandrel; the contact between the horn and the mandrel and the NdFeB sintered magnet is preferably rigid contact; the contact pressure between the horn and the mandrel and the NdFeB sintered magnet is preferably not less than 1.0×10 6 The contact area between the horn and the top rod and the NdFeB sintered magnet is preferably not less than 10mm independently. 2 The present invention limits the contact pressure and contact area between the horn and the top rod and the NdFeB sintered magnet to within the above range during the process of applying power ultrasound to the NdFeB sintered magnet, which can ensure that the horn and the top rod of the power ultrasound can stably clamp the NdFeB sintered magnet, ensure the smooth conduction of the power ultrasound, and further ensure the power ultrasound effect.
[0042] The present invention has no special limitation on the timing of the contact-introduced power ultrasonic treatment during the heat preservation process of the first heat treatment, the second heat treatment and the third heat treatment, and the same effect can be achieved by performing power ultrasonic treatment at any time during the heat preservation stage.
[0043] In the present invention, the power ultrasound preferably includes continuous ultrasound or pulsed ultrasound; in the present invention, the ultrasound power density of the power ultrasound is preferably (1-65)×10 4 W / m 3 , more preferably (5~40)×10 4 W / m 3 , and more preferably 6.4×10 4 W / m 3 The ultrasonic frequency of the power ultrasound is preferably 10-500kHz, more preferably 100-400kHz, and further preferably 200-300kHz. In the present invention, when the power ultrasound is pulsed ultrasound, there is no special requirement for the pulse change frequency of the pulsed ultrasound, and any pulse frequency can be used. The present invention limits the application mode of power ultrasound, ultrasonic power density and ultrasonic frequency to the above ranges, so that the NdFeB magnet has a high coercive force.
[0044] The present invention has no special limitation on the equipment for the first heat treatment, the second heat treatment and the third heat treatment, and any heat treatment device capable of realizing high-power ultrasound in an inert atmosphere and a high vacuum degree may be used.
[0045] In the present invention, the first heat treatment, the second heat treatment and the third heat treatment are preferably performed under an inert atmosphere; the gas selection and gas pressure selection of the inert atmosphere are the same as those of sintering, and will not be described in detail here.
[0046] In the present invention, the temperature of the first heat treatment is preferably 1000~1100℃, more preferably 1050℃; the time of the first heat treatment is preferably 0.5~4h, more preferably 2~4h, and further preferably 3~3.5h; the power ultrasonic time in the first heat treatment is preferably ≤ the time of the first heat treatment, more preferably 0.1~4h, and further preferably 1h. The present invention promotes the liquid grain boundary structure to fill the gaps between the magnetic phase grains and improves the degree of densification during the first heat treatment. The present invention sets the temperature, time and power ultrasonic time of the first heat treatment within the above range to further improve the coercive force of the NdFeB magnet.
[0047] In the present invention, the heating rate of the first heat treatment is preferably 5-20°C / min, more preferably 10-15°C / min. The present invention sets the heating rate of the first heat treatment within the above range to ensure uniform temperature rise in the green compact, which is beneficial to the performance of the magnet.
[0048] In the present invention, the cooling method, cooling medium and cooling speed of the first heat treatment are preferably the same as those of the cooling in the sintering process, and will not be described in detail here.
[0049] In the present invention, the temperature of the second heat treatment is preferably 800~950℃, more preferably 850~900℃, and further preferably 850℃; the time of the second heat treatment is preferably 2~3h, more preferably 2~2.5h; the power ultrasonic time in the second heat treatment is preferably ≤ the time of the second heat treatment, more preferably 0.1~3h, and further preferably 1h. The present invention promotes the uniform distribution of rare earth elements in the grain boundary structure during the second heat treatment, optimizes the spatial distribution of rare earth elements in the magnetic phase grains, increases the proportion of non-magnetic rare earth-rich phases, and reduces the proportion of paramagnetic REFe2 phases. The present invention sets the temperature, time and power ultrasonic time of the second heat treatment within the above range to further improve the coercive force of the NdFeB magnet.
[0050] In the present invention, the heating rate of the second heat treatment is preferably 5-20°C / min, more preferably 10-15°C / min. The present invention sets the heating rate of the second heat treatment within the above range to ensure uniform temperature rise in the green compact, which is beneficial to the performance of the magnet.
[0051] In the present invention, the cooling method, cooling medium and cooling speed of the second heat treatment are preferably the same as those of the cooling in the sintering process, and will not be described in detail here.
[0052] In the present invention, the temperature of the third heat treatment is preferably 400-600°C, more preferably 450-550°C, and further preferably 510°C; the time of the third heat treatment is preferably 3-4h, more preferably 3-3.5h; the power ultrasonic time in the third heat treatment is preferably ≤ the time of the third heat treatment, more preferably 0.1-4h, and further preferably 1h. The present invention makes the distribution of the rare earth-rich phase more uniform during the third heat treatment. The present invention sets the temperature, time and power ultrasonic time of the third heat treatment within the above range to further improve the coercive force of the NdFeB magnet.
[0053] In the present invention, the heating rate of the third heat treatment is preferably 5-20°C / min, more preferably 10-15°C / min. The present invention sets the heating rate of the third heat treatment within the above range to ensure uniform temperature rise in the green compact, which is beneficial to the performance of the magnet.
[0054] In the present invention, the cooling method, cooling medium and cooling speed of the third heat treatment are preferably the same as those of the cooling in the sintering process, and will not be described in detail here.
[0055] The present invention heat treats the NdFeB sintered magnet and performs power ultrasound during the heat preservation process, using ultrasound to change the physical and chemical environment in the high-temperature melt or solid phase, optimize the distribution of rare earth elements, promote the formation of uniform and continuous grain boundary structure, and optimize the content of rare earth-rich phase (α(RE)) and its distribution in the grain boundary structure, thereby improving the coercive force of the NdFeB magnet.
[0056] In an embodiment of the present invention, Figure 1 As shown, the temperature gradients of the sintering, the first heat treatment, the second heat treatment and the third heat treatment of the NdFeB magnet are:
[0057] Keep warm at 300~400℃ for 1~2h, then keep warm at 500~600℃ for 1~2h, then keep warm at 750~900℃ for 2~4h, then keep warm at 1000~1100℃ for 0.5~6h and then cool (sintering); keep warm at 1000~1100℃ for 0.5~4h, power ultrasonic for 0.1~4h and then cool (first heat treatment); keep warm at 800~950℃ for 2~3h, power ultrasonic for 0.1~3h and then cool (second heat treatment); keep warm at 400~600℃ for 3~4h, power ultrasonic for 0.1~4h and then cool (third heat treatment).
[0058] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Example 1
[0060] A method for improving the coercive force of NdFeB magnets by power ultrasonic treatment, comprising the following steps:
[0061] (1) Nd 9.19 Pr 3.06 Ce 16 Gd2Fe bal Al 0.05 Ga 0.1 Co 0.2 Cr 0.1 Ti 0.16 Zr 0.15 Cu 0.25 B 0.97 (wt%) and Nd 19.95 Pr 10.9 Fe bal Al 0.1 Ga 0.5 Co 0.5 V 0.01 Ti 0.03 Zr 0.08 Cu 0.36 B 0.84 (wt%) alloy powders were mixed in a mass ratio of 6:4 and pressed by isostatic pressing at 200 MPa in a 2T alternating pulse magnetic field to obtain a green compact;
[0062] (2) In an argon atmosphere with a pressure of 3×10 -3MPa, the green compact obtained in step (1) is heated from room temperature to a first holding temperature (330°C) at a heating rate of 10°C / min, sintered for 1 hour, then heated from the first holding temperature to a second holding temperature (600°C) at a heating rate of 10°C / min, sintered for 2 hours, then heated from the second holding temperature to a third holding temperature (800°C) at a heating rate of 10°C / min, sintered for 3 hours, then heated from the third holding temperature to a fourth holding temperature (1050°C) at a heating rate of 10°C / min, sintered for 2 hours, and then heated from the third holding temperature to a fourth holding temperature (1050°C) at a heating rate of 10°C / min, sintered for 2 hours, and then heated from the first holding temperature to a second holding temperature (600°C) at a heating rate of 10°C / min, sintered for 2 hours, and then heated from the second holding temperature to a third holding temperature (800°C) at a heating rate of 10°C / min, sintered for 3 hours, and then heated from the third holding temperature to a fourth holding temperature (105 ... second holding temperature to a third holding temperature (800°C) at a heating rate of 10°C / min, sintered for Ga-In-Sn liquid alloy was used as a cooling medium to cool to room temperature by liquid quenching; the sintered product was heated from room temperature to the first heat treatment temperature (1050°C) at a heating rate of 10°C / min and kept at this temperature for 2 hours, and then Ga-In-Sn liquid alloy was used as a cooling medium to cool to room temperature by liquid quenching; the product after the first heat treatment was heated from room temperature to the second heat treatment temperature (850°C) at a heating rate of 10°C / min and kept at this temperature for 2 hours. During the heat preservation process, a power density of 6.4×10 4 W / m 3 The product after the second heat treatment was subjected to contact-introduced power ultrasonic treatment for 1 hour, and then cooled to room temperature by liquid quenching using Ga-In-Sn liquid alloy as a cooling medium; the temperature of the product after the second heat treatment was raised from room temperature to a third heat treatment temperature (510°C) at a heating rate of 10°C / min, and kept warm for 3 hours, and then cooled to room temperature by liquid quenching using Ga-In-Sn liquid alloy as a cooling medium, to obtain a high coercive force NdFeB magnet.
[0063] Example 2
[0064] The difference between Example 2 and Example 1 is that the power density of the power ultrasound in the second heat treatment process is modified to 1.2×10 5 W / m 3 , the rest is the same as Example 1.
[0065] Example 3
[0066] The difference between Example 3 and Example 1 is that the power density of the power ultrasound in the second heat treatment process is modified to 3.8×10 5 W / m 3 , the rest is the same as Example 1.
[0067] Comparative Example 1
[0068] The difference between Comparative Example 1 and Example 1 is that power ultrasound is not performed during the second heat treatment process. The other steps are the same as Example 1 to obtain a NdFeB magnet.
[0069] The microstructure of the NdFeB magnets prepared in Example 1, Example 2, Example 3 and Comparative Example 1 was observed using a scanning electron microscope.
[0070] The magnetic properties of the NdFeB magnets obtained in Examples 1 to 3 and Comparative Example 1 were tested using an automatic permanent magnetic property measuring instrument.
[0071] The SEM image of the NdFeB magnet prepared in Example 1 is as follows: Figure 2 The SEM image of the NdFeB magnet prepared in Example 2 is shown in Figure 3 The SEM image of the NdFeB magnet prepared in Example 3 is shown in Figure 4 As shown, the SEM image of the NdFeB magnet prepared in Comparative Example 1 is as follows Figure 5 As shown, from Figures 2~5 It can be seen that compared with the NdFeB magnet obtained in Comparative Example 1, the volume proportion of the rare earth-rich phase (α(RE)) in the grain boundary structure of the NdFeB magnets of Examples 1 to 3 after power ultrasound is significantly increased, and the grain boundary structure distribution is more continuous and uniform, among which the α(RE) phase accounts for a larger proportion in Example 1. Figures 2~5 The volume proportion of the α(RE) phase in the comparative example 1 is 11.3%, the volume proportion of the α(RE) phase in the embodiment 1 is 21.2%, the volume proportion of the α(RE) phase in the embodiment 2 is 19.0%, and the volume proportion of the α(RE) phase in the embodiment 3 is 14.1%. The α(RE) phase proportion curve in the grain boundary structure of the NdFeB magnets prepared in the embodiment 1, the embodiment 2, the embodiment 3 and the comparative example 1 is as shown in Figure 6 shown.
[0072] The test data of magnetic properties of the NdFeB magnets obtained in Examples 1 to 3 and Comparative Example 1 are shown in Table 1.
[0073] Table 1 Magnetic properties test data of NdFeB magnets obtained in Examples 1 to 3 and Comparative Example 1
[0074]
[0075] It can be seen from Table 1 that compared with the NdFeB magnet prepared in Comparative Example 1, the intrinsic coercive force ( H cj ) were significantly improved, from 9.76kOe to 11.79kOe, 11.38kOe and 10.85kOe respectively.
[0076] The method provided by the present invention can significantly increase the volume proportion of the rare earth-rich phase (α(RE)) in the grain boundary structure of the NdFeB magnet to 21.2%, which is 87.6% higher than that of the NdFeB magnet without power ultrasound. H cj It can reach 11.79kOe, which is 20.8% higher than that of NdFeB magnets without power ultrasound, and can further improve the coercive force of NdFeB magnets.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the coercive force of NdFeB magnets by power ultrasonic treatment, characterized in that: Conducting contact-type power ultrasonic treatment during the heat preservation process of the NdFeB sintered magnet; The method for improving the coercive force of NdFeB magnets by power ultrasonic treatment comprises the following steps: The NdFeB sintered magnet is subjected to a first heat treatment, a second heat treatment and a third heat treatment in sequence to obtain a high coercive force NdFeB magnet; during the heat preservation process of at least one of the first heat treatment, the second heat treatment and the third heat treatment, a contact-introduced power ultrasonic treatment is performed; The power ultrasound includes continuous ultrasound or pulsed ultrasound; the ultrasound power density of the power ultrasound is (1-65)×10 4 W / m 3 , the ultrasonic frequency of power ultrasound is 10~500kHz; The power ultrasound is applied to the NdFeB sintered magnet in a contact manner through an ultrasonic system; the ultrasonic system includes a horn and a mandrel; the NdFeB sintered magnet is fixed between the horn and the mandrel; the contact mode between the horn and the mandrel and the NdFeB sintered magnet is rigid contact; the contact pressure between the horn and the mandrel and the NdFeB sintered magnet is not less than 1.0×10 6 The contact area between the horn and the top rod and the NdFeB sintered magnet is independently not less than 10mm 2 .
2. The method according to claim 1, characterized in that The shape of the NdFeB sintered magnet is to have at least two parallel end faces, and the two parallel end faces have an overlapping portion in projection; the area of the overlapping portion is not less than 10mm 2 .
3. The method according to claim 1, characterized in that: The temperature of the first heat treatment is 1000-1100° C., the holding time of the first heat treatment is 0.5-4 hours, and the time of the power ultrasound in the first heat treatment is ≤ the holding time of the first heat treatment.
4. The method according to claim 1, characterized in that: The temperature of the second heat treatment is 800-950° C., the insulation time of the second heat treatment is 2-3 hours, and the time of the power ultrasound in the second heat treatment is ≤ the insulation time of the second heat treatment.
5. The method according to claim 1, characterized in that: The temperature of the third heat treatment is 400-600° C., the insulation time of the third heat treatment is 3-4 hours, and the time of the power ultrasound in the third heat treatment is ≤ the insulation time of the third heat treatment.
6. The method according to claim 1, characterized in that The first heat treatment, the second heat treatment and the third heat treatment are all carried out under an inert atmosphere; the pressure of the inert atmosphere is less than 1×10 -2 Pa.
7. The method according to claim 1, characterized in that The cooling rates of the first heat treatment, the second heat treatment and the third heat treatment are independently greater than 20° C. / min.
8. The method according to claim 7, characterized in that The cooling methods of the first heat treatment, the second heat treatment and the third heat treatment are independently air cooling or liquid quenching; the cooling medium used for the liquid quenching is water, oil or liquid alloy.
Citation Information
Patent Citations
Preparation method of high-performance sintered neodymium-iron-boron magnet
CN111243806A
Grain boundary diffusion process of neodymium-iron-boron magnet and preparation method of neodymium-iron-boron magnet
CN114188143A
Method for preparing neodymium-iron-boron permanent magnet alloy powder
CN104439258A
Permeation method of sintered neodymium-iron-boron magnet and high-performance sintered neodymium-iron-boron magnet
CN115798916A